Electrical Energy Efficiency Improvement in Chiller Operation - Indrianto Sudjoko, Rifdian; Hartono, Hartono; Kustori, Kustori; Hariyadi, Slamet; Faizah, Fiqqih (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The need for electrical energy to meet consumers is increasing which must be addressed immediately. Along with population growth and economic growth, this energy need will continue to increase. With the use of large amounts of electrical energy, it is necessary to increase efficiency in operating equipment. Airports are one of the largest users of electricity, especially when it comes to cooling systems. Therefore, it is necessary to save energy in airport operations. Airports are one of society’s activities, so airports need to save energy. By optimizing power management and calculating the chiller coefficient of performance (COP) value, an airport can be built that saves energy on the HVAC system (especially chillers). Through analysis, it was found that COP increased to 0.584, and the value before optimization was 6.181. As COP increases, chiller performance will increase. The optimized electrical energy efficiency of the cooler is 138.82 kWh / day.